(untitled) (Third Sector Social Economic Review, 2021)
The main aim of this study is to measure the attitudes of insurance customers and agency employees in the insurance sector towards digitalization. An online survey was conducted with insurance customers and insurance agency employees operating in Ankara province. The survey study was applied by simple random sampling method to 390 insurance customers and 261 agency employees operating in TOBB registered agents. The results obtained from the survey were encoded into the SPSS 24 program. Statistical analysis conducted through this program, were chi-square test, nonparametric Spearman correlation test and Kruskal Wallis test. In addition to these tests, statistics such as proportional distributions, mean, frequency, standard deviation were calculated. As a result of the research, it is concluded that digital transformation is a requirement and should be developed. With digitalization, which remains an important requirement for the insurance industry, insurance companies have to adapt to the new environment, the new demands of customers and all the possibilities that arise with transformation. In the process of technological progress, insurance companies need to adopt changes more quickly and adapt to new technologies if they want to grow or at least maintain a presence.